The democratic road to socialism (again): strategies of Anglo-American democratic socialism 2015-2020 - Friend, C (2022)
This thesis attempts to assess the strategic questions and possibilities raised by the coming to prominence of ‘democratic socialism’ in the UK and US in 2015- 2020, with the rise of Jeremy Corbyn and the Labour left on the one hand, and of the Democratic Socialists of America, spurred on by the campaigns of Bernie Sanders, on the other. In doing so, it also hopes to give readers an account of what, in fact, ‘democratic socialism’ constitutes in the contemporary Anglo-American context, and, crucially, make out what might productively differentiate it from other socialist orientations on the question of strategy. In particular, the thesis argues that contemporary democratic socialism presents a coherent answer to a key strategic challenge: how, given the dual improbability of either a revolutionary or moderate, gradualist method of socialist transformation, to proceed as a socialist actor seeking transformational change in the context of a capitalist democracy. However, whether democratic socialism presents a convincing answer to this challenge, the thesis argues, is open to debate.